Perlakuan Post Weld Heat Treatment (PWHT)) Baja SS400 Terhadap Kekerasan Dan Struktur Mikro: Post Weld Heat Treatment (PWHT) of SS400 Steel on Hardness and Microstructure - M.Izza Hazazi; Sudirman Lubis (Jurnal Pendidikan Teknik Mesin Undiksha, 2025)
Write the abstract in English here. If articles in English, abstract in Indonesia language do not need to be included. Writing abbreviations and mathematical formulas in the abstract needs to be avoided. The abstract consists of summary of the research objectives, approaches or methods used, important results and conclusionsPost weld heat treatment (PWHT) has a significant influence on the mechanical properties and microstructure of low carbon steel, especially in the Base Metal, Heat-Affected Zone (HAZ), and Weld Area regions. This study aims to analyze changes in hardness and microstructure due to PWHT at 400°C, 500°C, and 600°C. The hardness test results show that at 400°C there was an increase of 24.5 HV in the Base Metal, 8.9 HV in the HAZ, and a decrease of 5.4 HV in the Weld Area. At 500°C, the increase in hardness was more significant with a value of 28.7 HV in the Base Metal, 19.8 HV in the HAZ, and a decrease of 15 HV in the Weld Area. However, at 600°C, the Base Metal decreased in hardness by 21.6 HV, the HAZ remained stable without change, and the Weld Area decreased by 17 HV. Microstructure analysis shows that PWHT at 500°C produces more significant changes than other temperatures, with greater growth of ferrite and pearlite phases. This is in line with the increase in hardness in the Base Metal and HAZ areas. In addition, observations showed that a welding current of 130A provided optimal penetration, resulting in a good metallurgical bond between the weld metal and the base metal. Thus, this study confirms that PWHT can be utilized to control the hardness and microstructure of materials to improve the quality of welded joints in low carbon steel